Therapeutic potential of boric acid as a local drug delivery agent in periodontitis: a comprehensive systematic review and meta-analysis - Reham Abdel-Fatah; Ghada A. Elhusseiny; Wafaa Saleh (BMC Oral Health)
Abstract Objective This systematic review and meta-analysis aim to evaluate the therapeutic potential of boric acid as a local drug delivery agent in the treatment of periodontitis. Methods Following PRISMA guidelines, we registered a comprehensive protocol with PROSPERO. By employing PICOS criteria, we evaluated randomized controlled trials assessing the effects of subgingival boric acid application alongside non-surgical periodontal therapy in treatment of periodontitis. Studies were systematically searched across multiple databases, with establishment of the eligibility criteria. Data extraction and risk of bias assessment were conducted independently by reviewers. Results Among 1,640 records screened, 6 studies met the inclusion criteria, comprising 281 participants aged 18–65 years. At 1-month, boric acid demonstrated significant improvements in probing pocket depth (PPD), but insignificant differences were observed in clinical attachment level (CAL), and gingival index (GI). However, at 3 and 6 months, we found significant reductions in PPD while at 6 months, a significant increase in CAL gain were observed favoring boric acid. No significant changes in GI were noted at any follow-up duration. Conclusion Boric acid adjunctive therapy in non-surgical periodontal treatment shows promising efficacy in improving clinical parameters, particularly PPD and CAL, over time. While early outcomes may not show significance, sustained benefits are evident at longer follow-up periods. These findings underscore the potential of boric acid as a valuable addition to periodontal therapy, demanding further investigation to reveal its precise mechanisms and optimize clinical application.